2021
DOI: 10.3233/adr-200292
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Response to an Online Dementia and Caregiver Wellness Education Platform

Abstract: Background: Web-based educational interventions are emerging as a potential solution to improving caregiver dementia knowledge and overall well-being. Objective: To assess the feasibility of delivering a web-based intervention for dementia caregivers by examining: 1) engagement with the online platform, 2) skill implementation, and 3) changes on outcome metrics over the 30-day study period. Methods: Enrolled participants were onboarded by a trained research coordinator and provided 24/7 access to the platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Further, the results based on two included studies showed that remote interventions had no potential benefits on depressive and anxiety symptoms in care recipients. The conclusion of this review is consistent with that of previous studies on the impact of remote interventions on other diseases 37 38…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, the results based on two included studies showed that remote interventions had no potential benefits on depressive and anxiety symptoms in care recipients. The conclusion of this review is consistent with that of previous studies on the impact of remote interventions on other diseases 37 38…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in our included studies, the severity of patients who had a stroke was inconsistent, and if the degree of illness of patients was different, the burden of caregivers may also be different. The study by Rodriguez et al indicated that the effect of remote interventions on caregivers of patients with different disease severity levels should be evaluated because it may be tied to different levels of caregiver burden 37. Meanwhile, in the eight included studies in our review, the specific content of remote interventions was mainly based on the experience of different intervention makers and previous literature, ignoring the preferences and needs of patients who had a stroke and their informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-five papers covering 49 studies were included (some studies were demonstrated in a series of papers). The included studies consisted of 19 RCTs [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 10 non-RCTs [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ], 4 descriptive quantitative studies [ [57] , [58] , [59] , [60] ], 4 qualitative studies [ [61] , [62] , [63] , [64] ] and 12 mixed-methods studies [ [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ], see Appendix A . These studies were conducted in America ( n = 25), Netherlands ( n = 4), Canada ( n = 2), France ( n = 1), India ( n = 1), China ( n = 1), Australia ( n = 3), United Kingdom ( n = 2), Spain ( n = 1), Greece ( n = 1), Ireland ( n = 1), Korea ( n = 1), Iran ( n = 1) and multiple European countries ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Family caregivers desired more detailed information, such as stage-specific dementia information, attention to more difficult behaviors and complex issues, end-of-life planning and local resource [ 46 , 49 , 67 , 69 , 73 , 74 ]. Five studies perceived that more culturally, ethnically, or gender-related components may influence the delivery of online educational programs [ 28 , 34 , 39 , 54 , 76 ]. Even so, the results showed that 4 studies explored the impact of online educational programs on family caregivers’ knowledge relating to dementia [ 35 , 47 , 50 , 67 ], with 3 of them finding positive improvements.…”
Section: Resultsmentioning
confidence: 99%